The monkey and bananas problem revisited: a situation calculus approach - Simari, Gerardo I. (2003)
This work develops a complete example of how to obtain a Situation Calculus Action Theory. The problem selected is a simple one, yet it is enough to cover the important details of the process without unnecessary complications. After obtaining the action theory, a running Prolog program is derived from the axioms: at this point, some problems, and a proposed solution, are presented.